2019
DOI: 10.1152/ajpendo.00096.2019
|View full text |Cite
|
Sign up to set email alerts
|

eNOS deletion impairs mitochondrial quality control and exacerbates Western diet-induced NASH

Abstract: Dysregulated mitochondrial quality control leads to mitochondrial functional impairments that are central to the development and progression of hepatic steatosis to nonalcoholic steatohepatitis (NASH). Here, we identify hepatocellular localized endothelial nitric oxide synthase (eNOS) as a novel master regulator of mitochondrial quality control. Mice lacking eNOS were more susceptible to Western diet-induced hepatic inflammation and fibrosis in conjunction with decreased markers of mitochondrial biogenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 57 publications
(70 reference statements)
3
36
0
Order By: Relevance
“…Using an advanced liquid chromatography tandem mass spectrometry approach, they clearly identified eNOS in their purified hepatocytes, with its highest expression in Kupffer cells and liver sinusoidal endothelial cells. Using the same methodology, our group has confirmed these findings by identifying eNOS expression in isolated primary hepatocytes from WT mice using magnetic-activated cell sorting and immunofluorescence ( Sheldon et al, 2019 ). Taken together, these more recent and methodologically robust data strongly imply the presence of eNOS in hepatocytes.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Using an advanced liquid chromatography tandem mass spectrometry approach, they clearly identified eNOS in their purified hepatocytes, with its highest expression in Kupffer cells and liver sinusoidal endothelial cells. Using the same methodology, our group has confirmed these findings by identifying eNOS expression in isolated primary hepatocytes from WT mice using magnetic-activated cell sorting and immunofluorescence ( Sheldon et al, 2019 ). Taken together, these more recent and methodologically robust data strongly imply the presence of eNOS in hepatocytes.…”
Section: Introductionmentioning
confidence: 82%
“…Finally, hepatic TAG accumulation was increased with 4 weeks of NOS inhibition with the non-selective NOS inhibitor (N ω -nitro-L-arginine methyl ester; L-NAME), in hyperphagic OLETF rats ( Sheldon et al, 2015 ). Moreover, we also have shown that reduced eNOS activation is associated with NAFLD progression ( Sheldon et al, 2014 , 2019 ). Importantly, loss of eNOS activation, as well as NAFLD development, were prevented with chronic voluntary wheel running exercise, indicating a potential role for exercise-induced elevations in eNOS activity in liver health ( Sheldon et al, 2014 ).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The mitochondrial quality control (MQC) mechanism involves intricate regulation of several processes such as proteostasis, biogenesis, dynamics, and mitophagy, all of which are integral to maintaining cellular homeostasis as shown in Figure 2 [5][6][7]. The failure of the quality control processes results in mitochondrial dysfunction and is one of the underlying causes for NAFLD [8]. MQC involves coordinated regulation of a hierarchical network of pathways that act sequentially from an individual protein molecule to the whole organelle [9][10][11].…”
Section: Introductionmentioning
confidence: 99%